Sistema de indicadores de control para mejorar la gestión de proyectos en la incubadora de una universidad privada, Trujillo, 2021 - Sinche Gutiérrez, Adriana Sofía (2023)
The main objective of this research was to verify that a control indicator system improves project management in the incubator of a private university in Trujillo. For this purpose, a descriptive quantitative research methodology was used with a pre-experimental design that allowed analyzing the study sample formed by all the employees, clients (entrepreneurs), and the processes carried out in the business incubator, for which an interview and a documentary review were applied in order to collect data to diagnose the current situation of the organization. The results showed that the current situation of the business incubator has problems in the performance of project management with low performance, thus leading to propose a system of control indicators to improve the performance of management in the business incubator. It was then verified whether the proposal had an impact on the improvement of the processes, concluding that the design of a system of control indicators does improve the project management of a university incubator. Finally, it was recommended to continue with the use of indicators to promote continuous improvement.